Invertebrates in ecosystem restoration: Thirty years of research in land rehabilitation following mining - Majer, Jonathan; Brennan, K. E. C.; Moir, M. L. (2007)
Restoration needs to consider more than just soils and plants. The role of terrestrial invertebrates in the restoration of Alcoa’s bauxite mines in the Jarrah (Eucalyptus marginata) forest of Western Australia has been the subject of over 20 individual studies. Projects range from arthropods in soil and leaf litter, to the understorey vegetation, and the tree canopy. Moreover, projects span a range of trophic groups, including decomposers (e.g., springtails and termites), predators (e.g., ants and spiders), and herbivores (e.g., true bugs and ants preying on seeds). Elucidation of recolonization trajectories uses both space-for-time substitutions and long-term regular sampling. Importantly, many studies are at species level rather than coarser taxonomic ranks. This paper provides an historical account and an integrated review of this research. The role of ants as seed predators and as indicators of ecosystem health is described.